Explanation of anomalous rate capability enhancement by manganese oxide incorporation in carbon nanoﬁber electrodes for electrochemical capacitors. (20th April 2020) - Li, Qi; Kuzmenko, Volodymyr; Haque, Mazharul; Di, Mengqiao; Smith, Anderson D.; Lundgren, Per; Enoksson, Peter
Abstract: Electrochemical capacitors (ECs) can provide ultra-long cycle life and ultra-fast energy delivery, characteristics which most battery technologies lack. Making composites out of carbon and pseudocapacitive materials is a popular strategy directed on narrowing the gap in energy density with regard to batteries. Usually, the incorporation of pseudocapacitive materials leads to a decrease in power performance compared to a pure carbon matrix, due to inferior electrical conductivity. This work, however, presents signiﬁcant improvement in rate capability demonstrated by a composite electrode containing carbon nanoﬁbers (NCNF) and manganese oxides (MnO2 ). The NCNF/MnO2 is prepared with a common method through the reaction with permanganate. The material has excellent performance metrics, especially a 78.2% rate capability (capacitance retention at 15 A g −1 relative to 0.5 A g −1 ), more than 10 times that for the NCNF carbon matrix. The exceptional enhancement can be explained by the development of micropores and surface area of NCNF, thus alleviating the "pore starvation" issue, and surface functional groups variation that enhances capacitive performance. This work highlights the importance of paying attention to the modiﬁcation of carbon substrate when investigating carbon composite electrodes e.g. carbon/MnO2 networks. Highlights: N-doped carbon nanofiber (NCNF) electrodes were derived from cellulose. Compositing NCNF with MnO2 led to surprising enhancement in rate capability. 88.8 F g −1 capacitance was obtained at 15 A g −1 for the composite electrode. Porosity and surface chemistry of NCNF were improved during compositing.